Det attende århundredes islandske leksikografi - Kvaran, Guðrún (LexicoNordica, 2000)
This paper deals with 18th century lexicography in lceland. At that time intere~t in lcelandic dictionaries began to grow, especially due to the influence of professor Arni Magnusson in Copenhagen. Several still unpublished lexicographical manuscripts of historical value from thi~ period exist, the most important one being the lcelandicLatin Dictionary of J6n Olafsson from Grunnavik (AM 433 fol.) with about 50.000 entries. Only two dictionaries were published at this time, howe'!er, a Latin-Icelandic dictionary (1738), Nucleus Latinitatis, compiled by bishop J6n Amason, and the lcelandic- Latin-Danish dictionary (1814) of Bjom Halld6rsson with Danish translations by Rasmus Christian Rask. The latter work in particular had strong influence on most lcelandic dictionaries in the 19th and 20th century.